Modeling, Analysis and Optimization for Mathematical Finance, Economics and Risks - Jing Yao; Xiang Hu; Jingchao Li (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Modeling, Analysis, and Optimization for Mathematical Finance, Economics, and Risks is a critical domain that integrates mathematical theory with practical applications to address the complexities of modern financial and economic systems. This special issue focuses on recent studies that are helping to develop sophisticated mathematical models to better understand, predict, and optimize financial markets, economic behaviors, and risk management. These studies, as well as the theoretical results and practical applications contained in this reprint, underscore the importance of a rigorous, quantitative approach to navigate and master the intricacies of these interconnected fields. This synergy not only advances theoretical understanding but also drives practical innovations, ensuring robustness and resilience in a rapidly evolving global landscape of modern quantitative techniques for financial mathematics, actuarial science and operational research.
Keywords: 330; default risk; ambiguity aversion; HJB equation; optimal investment; (p; q; m)-core inverse; 〈p; q; n〉-core inverse; 〈i; m〉-core inverse; (j; m)-core inverse; core inverse; DMP-inverse; core-EP inverse; two-sided jumps; Gerber–Shiu function; Laguerre series; estimator; skew diffusion process; perturbed diffusion process; perturbed skew diffusion process; local time; change in time; bidimensional perturbed risk model; correlated brownian motions; finite-time ruin probability; heavy-tailed risk model; interest force; DC pension plan; stochastic volatility; Poisson process; common shock dependence; inflation; Hamilton–Jacobi–Bellman equation; automobile insurance; generalized additive models; splines; tariff analysis; transience; recurrence; CIR model; time-dependent region; reflection; portfolio optimization; robustness; sparsity; uncertainty set; penalty-alternating-direction method; dividend payment; model ambiguity; optimal debt ratio; financial preparedness; emergency fund; machine learning; consumer studies; M-CEV model; expected utility; HARA; ambiguity-aversion; Cauchy problem; vine copula grouped model; CoES; systemic risk; rolling of Monte Carlo simulation; queuing system; impatient customers; optimization; pricing strategy